The Influence Of Transformational Leadership And Competence On Employee Performance Through Readiness To Change In Badung Pamong Praja Police Unit - Ardana, I Made; Wiles, Erna Zulaeni; Mekarini, Ni Wayan (Jurnal Scientia, 2024)
This research aims to determine the influence of transformational leadership, competency and readiness to change on employee performance at the Badung Satpol PP, then to determine the influence of transformational leadership and competency on readiness to change, then to determine the influence of transformational leadership and competency on employee performance through readiness to change. changed at Badung Satpol PP. The sampling technique uses a purposive sampling method. The population in this study is all employees of the Badung Regency Civil Service Police Unit in 2024, totaling 288 employees. The type of data used in this research is quantitative data. The data source in this research is primary data. Data analysis in this research uses the Partial Least Square (PLS) approach using SmartPLS software, namely SmartPLS 4.0. The research results show that, 1) Transformational leadership has a positive and significant effect on employee performance, 2) Competency has a positive and significant effect on employee performance, 3) Readiness to change has a positive and significant effect on employee performance, 4) Transformational leadership has a positive and significant effect on readiness to change, 5) Competence has a positive and significant effect on readiness to change, 6) Readiness to change is able to mediate the influence of transformational leadership on employee performance, and 7) Readiness to change is able to partially mediate the influence of competence on employee performance.